Ekspansi Perkotaan di Surabaya Metropolitan Area: Alami atau Terrencana? - Belinda Ulfa Aulia (Jurnal Penataan Ruang, 2025)
Abstract: The growth of metropolitan areas in Indonesia has driven the expansion of urban spaces into peripheral regions, giving rise to increasingly intense suburbanization in major cities such as Jakarta, Surabaya, and Bandung. Suburbanization not only reflects spatial shifts due to population growth but also results from spatial planning policies that actively promote land conversion in urban fringes. This article highlights the role of land-use plans as policy instruments that influence the direction and pattern of suburban development, with a case study focusing on the Surabaya metropolitan area, particularly Sidoarjo and Gresik Regencies. Spatial analysis reveals that built-up area expansion over the past two decades has largely occurred in zones designated for residential use in each regency's spatial plan (RTRW), indicating a strong alignment between planning and development outcomes. However, this alignment also reveals that spatial plans function more as facilitators of expansion rather than as mechanisms for development control. As a result, suburban growth in these areas tends to be fragmented and is not always accompanied by adequate infrastructure provision or spatial integration. These findings support the argument that suburbanization in Indonesia is a politically and economically produced process, rather than a mere outcome of market dynamics. The article recommends a more strategic, integrated, and critical planning approach toward zoning objectives so that spatial planning can serve as a tool for equitable and sustainable metropolitan development. Suburbanisation; Urban growth; Metropolitan.